Mock-up: An Aid in the Different Steps in Aesthetic Dental Treatment - Dragusha, Rozafa; Ibraimi, Djemal (European Scientific Journal, ESJ, 2016)
Today, in restorative and prosthodontic dental treatments, the focus is on aesthetics. This involves meeting the needs and expectations of the patient. Failures occur not only as a result of technical problems, but also as a result of poor communication with the patient. To avoid these scenarios that may obligate us to repeat the restoration from the beginning, we can obtain help by using Mock-up. Despite communication with the diagnostic and treatment planning step, Mock-up enables us to control the function of the end result without even beginning the work. It also enables us to do a minimal invasive tooth preparation. The aim of this study is to use Mock-up to show its effectiveness in communication, planning, and preparation to achieve the demanded aesthetic dental treatment. Materials and Methods: We prepared mock-up according to wax-up in the second meeting- the treatment planning step. We used a minimal invasive, mock-up guided, preparation technique from the Mock-up accepted by us and the patient. Results: This easy and practical method enabled us to avoid the intervention in the ultimate restoration. Our result is in accordance with those of other authors: we had minimal preparation, even some unprepared surfaces and satisfied patient. Conclusions: The use of Mock-up is a simple technique in aesthetic dentistry. Broadly in prosthodontics, it assures us that the work will be functionally and aesthetically successful.